A Mixed-Methods Evaluation of an Iron Supplementation Program for Adolescent Girls in Magelang City - Ganap, Eugenius Phyowai; Rahmalina, Rahmalina; Dwi Cahyanti, Ratnasari; Hari Respati, Supriyadi (Indonesian Journal of Obstetrics and Gynecology, 2025)
AbstractObjective: To evaluate the implementation of the iron supplementation program for adolescent girls in Magelang City andidentify supporting and inhibiting factors.Methods: This study used a mixed-methods triangulation design with purposive sampling. Quantitative data from the MagelangCity Health Office were analyzed descriptively, while qualitative data from interviews and FGDs explored implementationbarriers.Results: The program achieved 72.2% coverage, meeting the national target. Supporting factors included regulatory planning,digital reporting via e-PPGBM, cross-sectoral collaboration, and the Aksi Bergizi initiative. However, barriers such as lack ofbudget, SOPs, human resources, and low adherence were identified.Discussion: Quantitative findings provided an overview of program success, while qualitative insights revealed operationalchallenges. Low adherence was influenced by limited awareness, unclear benefits, and perceived barriers like nausea and lackof parental support. Reporting delays and system closures also hindered performance.Conclusion: Despite meeting coverage targets, the program faces significant implementation challenges. Strengtheningbudgeting, SOPs, and human resources, along with improving adolescent awareness, is essential for future success.Keywords: Adolescent girls, iron supplementation, mixed-methods study, program evaluation.